Fuzzy Stack Filters for Image Processing - Marchevsky, S.; Stupak, Cs. (Radioengineering Society, 1999)
This paper is oriented to filtering by fuzzy stack filter of monochromatic images distorted with impulsive noise. Fuzzy stack filter is acquired by extension of stack filters by means of fuzzy logic. Adding some parameters to this filter, that are adjusted by neural adaptation algorithm, is obtained the new class of filters, so-called fuzzy rank-order filters. This class of filters is compared with other well known filters as stack filters and neural stack filters.
Keywords: image processing; stack filter; fuzzy logic; median filter; neural filter; genetic algorithm